The Impact of Quality of Banking Services on the Customer Satisfaction in Small and Medium Banks - Alall, Hussein Adnan Essa (South Asian Journal of Social Sciences and Humanities, 2024)
The study aims to test the nature of the association between the quality of banking services  and its role in achieving customer satisfaction. This study tested the quality of banking  services in south Asian countries and identified the various relative importance’s representing  the quality of banking services. The study included a purposive sample of commercial banks  from 139 individual banks, and the study used statistical software STATA to analyse the  results. The results presented that there is a positive and important association among the  quality of banking services and customer satisfaction. As a result of these challenges, it has  become necessary for banking organizations to take into account the philosophy of customer  satisfaction, which provides them with a competitive advantage that contributes to achieving  high level of profitability.
Keywords: Quality of Banking Services; Customer Satisfaction; Small and Medium Banks